Answer:
x = -3 , y = 0
Explanation:
Solve the following system:
{4 x - y = -12 | (equation 1)
-x - y = 3 | (equation 2)
Add 1/4 × (equation 1) to equation 2:
{4 x - y = -12 | (equation 1)
0 x - (5 y)/4 = 0 | (equation 2)
Multiply equation 2 by 4/5:
{4 x - y = -12 | (equation 1)
0 x - y = 0 | (equation 2)
Multiply equation 2 by -1:
{4 x - y = -12 | (equation 1)
0 x+y = 0 | (equation 2)
Add equation 2 to equation 1:
{4 x+0 y = -12 | (equation 1)
0 x+y = 0 | (equation 2)
Divide equation 1 by 4:
{x+0 y = -3 | (equation 1)
0 x+y = 0 | (equation 2)
Collect results:
Answer: {x = -3 , y = 0